The curse of the cheese pyramid - Dami, Elisabetta (New York Scholastic, 2004)
Geronimo travels to Egypt to interview Professor Alrat Spitfur and learns the secret of the Seven Wonders of the Ancient Mouse World.
H
"English translation... by Edizioni Piemme S.p.A."--T.p. verso.
b
b
Keywords: Dami, Elisabetta -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Pyramids -- Fiction; Journalists -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Egypt -- Fiction